Nutrient Composition of Four Species of Grasshoppers from Alpine Grasslands in the Qilian Mountain of the Tibetan Plateau, China - Sun, Tao; Shang, Zhanhuan; Liu, Zhiyun; Long, Ruijun (2010)
The study was conducted to determine the nutritional composition of four dominant species of grasshoppers, Oedalius asiaticus, Angaracris rhodopa, Chorthippus dubius and C. fallax (Orthoptera: Acrididae), found in the alpine grasslands in the Qilian Mountain of the Tibetan plateau, China in order to provide a basis for using grasshoppers as feeds for grazing chicks to modulate grasshopper population densities in the grasslands. Proximate analyses results were variable, with wide ranges found for moisture (64.9-71.4%), crude protein (62.4-67.2%), crude fat (4.8-6.8%), crude fiber (7.0-9.2%) and ash (4.1-4.7%), dry matter (DM) basis. Energy content ranged from 3923-4018 kcal kg(-1) DM. The four grasshopper species had a low calcium content, less than one-tenth of the dietary levels recommended by the National Research Council (NRC). Based on an amino acid scoring pattern for chicks, the first limiting amino acid for the four grasshopper species appears to be the sulfur amino acid methionine + cystine. The percent of unsaturated fatty acid in total fat ranged from 75.3-79.7%, especially linolenic acid (25-30.3%) and oleic acid (26.6-30.1%).
Keywords: Grasshopper; Grassland ecology